Integrating minimalism and Chinese cultural elements in new product design - Yi, Wang (2025)
Culture plays a pivotal role in the branding and commercialisation of products in global market. This research investigates the intersection of minimalism and Chinese cultural element in the product design for BANG & OLUFSEN (B&O), a luxury audio brand recognised for its minimalist design, and its resonance with Chinese consumers. The research aims to evaluate the practical application of minimalist design and Chinese cultural elements in B&O products and their influence on brand recognition in the Chinese market. This research employs a qualitative research method to examine the integration of minimalist design and Chinese cultural elements in B&O products. Data were collected via questionnaires and in-depth interviews to explore users’ emotional connections and cultural acceptance. Then, analysed thematically to identify key design and cultural themes. The research sample comprises of two design experts and one cultural studies expert. Besides that, this research also includes twenty loyal and potential market users. Interview analysis reveals that B&O’s minimalist design in the Chinese market focus on simplicity, functionality, and quality. Cultural adaptability and user feedback significantly influence product acceptance. Traditional patterns, symbols, colours, materials, and modern design techniques are the most suitable cultural elements for integration. Enhancing brand recognition strengthens consumer identity and affinity, fostering brand loyalty. Users increasingly prefer products that reflect cultural connotations while aligning with modern aesthetics. This study contributes to both theoretical understanding and practical applications. It demonstrates that the integration of minimalist design and Chinese cultural elements enhances brand acceptance in the Chinese market. Incorporating cultural elements also strengthens consumer cultural identity and fosters brand loyalty. Practical design strategies for successful integration are proposed, including element integration and balancing tradition with innovation